FINGERPRINTS: HISTORY AND TODAY - Abdurashid Abdumannobovich Turgunov (American Journals Publishing, 2023)
This article provides an overview of the science of fingerprints, including their detection and identification. We discuss the anatomy of fingerprints and the various types of prints that can be left at a crime scene. We also describe the various methods used to detect fingerprints, including traditional methods such as dusting and newer and DNA analysis. The article also explores the process of fingerprint identification, which involves comparing a fingerprint found at a crime scene to a known fingerprint database.
Keywords: fingerprint, patterns, furrows, loops, vortices, arcs, ridges, dermatoglyphics.